2022
DOI: 10.3389/fpubh.2022.873769
|View full text |Cite
|
Sign up to set email alerts
|

Using implementation mapping to develop strategies for preventing non-communicable diseases in Japanese small- and medium-sized enterprises

Abstract: IntroductionWorkplace programs to prevent non-communicable diseases (NCDs) in the workplace can help prevent the incidence of chronic diseases among employees, provide health benefits, and reduce the risk of financial loss. Nevertheless, these programs are not fully implemented, particularly in small- and medium-sized enterprises (SMEs). The purpose of this study was to develop implementation strategies for health promotion activities to prevent NCDs in Japanese SMEs using Implementation Mapping (IM) to presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…To the best of our knowledge, the eSMART-TC will be the first cluster randomized control study to apply a hybrid type II design to evaluate the bundle of three implementation strategies (supporting employees through campaigns, tailored ongoing facilitation, and ensuring executive engagement and support) targeting employers and health managers. This study will build upon our previous work, which demonstrated that strong endorsement, support, and positive feedback from employers are important to promote the implementation of workplace health promotion [ 13 ], and identified strategies for SMEs in Japan following an implementation mapping protocol [ 26 ]. This study will allow us to determine whether interactive intervention for management can increase the implementation of tobacco control measures in SMEs where resources are generally limited and increase the uptake of evidence-based cessation methods (smoking cessation treatments, nicotine replacement therapy, and nicotine gum) among smoking employees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, the eSMART-TC will be the first cluster randomized control study to apply a hybrid type II design to evaluate the bundle of three implementation strategies (supporting employees through campaigns, tailored ongoing facilitation, and ensuring executive engagement and support) targeting employers and health managers. This study will build upon our previous work, which demonstrated that strong endorsement, support, and positive feedback from employers are important to promote the implementation of workplace health promotion [ 13 ], and identified strategies for SMEs in Japan following an implementation mapping protocol [ 26 ]. This study will allow us to determine whether interactive intervention for management can increase the implementation of tobacco control measures in SMEs where resources are generally limited and increase the uptake of evidence-based cessation methods (smoking cessation treatments, nicotine replacement therapy, and nicotine gum) among smoking employees.…”
Section: Discussionmentioning
confidence: 99%
“…A key strength of our study is that the content of the implementation intervention was developed based on a theoretical framework and formative research. The implementation strategies were developed by applying social cognitive theory, targeting barriers and facilitators identified by the Consolidated Framework for Implementation Research [ 13 , 26 ]. If the effectiveness of this intervention is confirmed, the approach of this intervention targeting management can be applied to other areas of the workplace, such as measures against hypertension and improving health check-up rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tasks of implementation mapping (IM) described by Fernandez et al (32) offer a systematic approach to developing an implementation plan by combining theory and co-creation with stakeholders in practice. IM has previously helped to identify implementation strategies for various preventive interventions and programmes (40)(41)(42)(43)(44)(45)(46). The five tasks of IM are the following: (1) conduct an implementation needs assessment to identify barriers and facilitators for implementation, (2) identify adoption and implementation outcomes, performance objectives, and change objectives, (3) select theoretical methods and design implementation strategies, (4) produce implementation protocols and materials, and (5) evaluate implementation outcomes (32).…”
Section: Theoretical Backgroundmentioning
confidence: 99%